Lithium slag recycled concrete
By modifying lithium slag powder with a specific liquid compound and ultrasonic treatment, the strength of concrete is maintained or improved, allowing for higher lithium slag content without strength loss, addressing the limitation of lithium slag in concrete applications.
Patent Information
- Application Number
- CN202411225447.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-20
AI Technical Summary
Lithium slag, when added in large quantities to concrete, significantly reduces its strength, limiting its application and utilization.
A lithium slag recycled concrete is produced by modifying lithium slag powder with a liquid compound of sodium secondary alkyl sulfonate, coconut oil diethanolamide, and nonanediol monomethyl ether, and subjecting it to ultrasonic vibration, which enhances its activity, allowing it to replace cement in large quantities without strength reduction.
The modified lithium slag powder can be added up to 50% in concrete, maintaining or increasing its strength, thereby overcoming the strength-decreasing effect of lithium slag and enhancing its economic value.
Smart Images

Figure BDA0005024365820000101 
Figure BDA0005024365820000111
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, in particular to lithium slag recycled concrete. Background Art
[0002] Lithium slag is waste produced during the smelting process of lithium ore. Its main components include silicon oxide, aluminum oxide and calcium oxide, etc. These components make lithium slag have certain resource utilization value.
[0003] In the prior art, lithium slag has been applied to concrete to partially replace cement. However, after lithium slag replaces cement, the increase in the amount of lithium slag added will lead to a decrease in concrete strength. For example, the research results of Zhang Yannian et al. on the mechanical properties and hydration mechanism of lithium slag-based multi-solid waste admixtures in the prior art show that when lithium slag, self-igniting coal gangue and steel slag are mixed, the strength of concrete will decrease when the amount is greater than 30%. However, the 30% amount does not mean that all lithium slag is used. It can be seen that the actual amount of lithium slag added is relatively low, resulting in a large limitation on the application of lithium slag. Therefore, there is still room for improvement. Summary of the invention
[0004] In order to reduce the impact on concrete strength when lithium slag is added in large quantities, the present application provides a lithium slag recycled concrete.
[0005] The lithium slag recycled concrete provided in this application adopts the following technical solution: A lithium slag recycled concrete, comprising the following components in parts by weight: 100 parts water; 140-145 parts of cement; 140-145 parts of modified lithium slag; 450-460 parts of fine aggregate; 625-635 parts of recycled coarse aggregate; Water reducing agent 4.5-4.7 parts; The modification method of the modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder; Step 2), mixing lithium slag powder and modifying liquid, immersing the lithium slag powder in the modifying liquid, and ultrasonically vibrating for 15-25 minutes; Step 3), filtering and drying to obtain modified lithium slag; In the step 2), the modified liquid is a compound of sodium secondary alkyl sulfonate, coconut oil diethanolamide, and nonanediol monomethyl ether.
[0006] By adopting the above technical scheme, the lithium slag powder is modified by using a modifying liquid prepared by mixing sodium secondary alkyl sulfonate, coconut oil diethanolamide and nonanediol monomethyl ether. Under the cutting action of ultrasonic waves, the activity of the lithium slag powder is greatly improved, so that after the lithium slag powder replaces cement in large quantities, the concrete formed has higher strength, overcomes the defect that the strength of the concrete decreases due to the addition of a large amount of lithium slag powder, and the lithium slag powder addition amount can be as high as 50%, reducing the restrictions on the application of lithium slag powder, and has higher economic value.
[0007] Preferably, the mass ratio of the sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water is 33-39:72-78:58-64:163-181.
[0008] By adopting the above technical scheme and specifically selecting the mass ratio of sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water, the effect of the modified lithium slag powder is better, the activity is better improved, and thus the strength of the concrete is higher.
[0009] Preferably, in step 2), the ultrasonic power is 1500-1800W.
[0010] By adopting the above technical solution and specifically selecting the ultrasonic power, the ultrasonic wave can better cut the lithium slag powder, so that the activity of the lithium slag is higher and the strength of the prepared concrete is higher.
[0011] Preferably, in the step 2), the lithium slag powder and the modified liquid are mixed, heated to 50-60° C., and then subjected to ultrasonic vibration.
[0012] By adopting the above technical solution and performing ultrasonic oscillation at 50-60°C, the activity of lithium slag is better improved, and the strength of concrete is further improved.
[0013] Preferably, the mass ratio of the cement to the modified lithium slag is 1:1.
[0014] By adopting the above technical solution, a large amount of lithium slag can be consumed, while the strength of concrete is less affected, and the lithium slag can be better utilized.
[0015] Preferably, the water reducer is a polycarboxylate water reducer.
[0016] By adopting the above technical solution and specifically selecting the polycarboxylate water-reducing agent, the water-reducing effect is better, the dosage is less, and the impact on the performance of the concrete is lower.
[0017] Preferably, the fine aggregate is 20-40 mesh.
[0018] By adopting the above technical solution and specifically selecting the size of fine aggregate, the concrete has a higher density and a higher strength.
[0019] Preferably, the particle size of the recycled coarse aggregate is 10-15 mm.
[0020] By adopting the above technical solution and specifically selecting the particle size of the recycled coarse aggregate, the effect of combining it with the fine aggregate is better, and the strength of the concrete is better improved.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application modifies the lithium slag powder by using a modifying liquid compounded with sodium secondary alkyl sulfonate, coconut oil diethanolamide and nonanediol monomethyl ether, the activity of the lithium slag powder is greatly improved under the cutting action of ultrasonic waves, so that the concrete formed after the lithium slag powder replaces cement in large quantities has higher strength, overcoming the defect that the strength of concrete decreases due to the addition of a large amount of lithium slag powder, so that the lithium slag powder addition amount can be as high as 50%, reducing the restrictions on the application of lithium slag powder, and having higher economic value.
[0022] 2. In the present application, it is preferred to specifically select the mass ratio of sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water to make the modified lithium slag powder more effective and improve the activity, thereby making the strength of the concrete higher. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments.
[0024] Example 1 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0025] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0026] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0027] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0028] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0029] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0030] Step 2), 339kg of sodium secondary alkyl sulfonate, 72kg of coconut oil diethanolamide, 58kg of nonane glycol monomethyl ether, and 163kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 163kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 50°C, and ultrasonically vibrated for 15min with an ultrasonic power of 1500W.
[0031] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0032] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0033] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0034] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0035] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0036] The preparation method of lithium slag recycled concrete is as follows: Step 01), 140kg cement, 140kg modified lithium slag, 450kg fine aggregate, 625kg recycled coarse aggregate, and 4.5kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0037] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0038] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0039] Example 2 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0040] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0041] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0042] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0043] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0044] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0045] Step 2), 36kg of sodium secondary alkyl sulfonate, 75kg of coconut oil diethanolamide, 61kg of nonane glycol monomethyl ether, and 172kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, and ultrasonically vibrated for 20min with an ultrasonic power of 1650W.
[0046] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0047] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0048] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0049] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0050] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0051] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0052] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0053] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0054] Example 3 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0055] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0056] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0057] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0058] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0059] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0060] Step 2), 39kg of sodium secondary alkyl sulfonate, 78kg of coconut oil diethanolamide, 64kg of nonane glycol monomethyl ether, and 181kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 181kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 60°C, and ultrasonically vibrated for 25min with an ultrasonic power of 1800W.
[0061] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0062] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0063] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0064] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0065] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0066] The preparation method of lithium slag recycled concrete is as follows: Step 01), 145kg cement, 145kg modified lithium slag, 460kg fine aggregate, 635kg recycled coarse aggregate, and 4.7kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0067] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0068] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0069] Comparative Example 1 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0070] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0071] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0072] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0073] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0074] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0075] Step 2), 36kg of fatty alcohol polyoxyethylene ether sodium sulfate, 75kg of coconut oil diethanolamide, 61kg of nonane glycol monomethyl ether, and 172kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, and ultrasonically vibrated for 20min with an ultrasonic power of 1650W.
[0076] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0077] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0078] Sodium fatty alcohol polyoxyethylene ether sulfate is commercially available, CAS number: 9004-82-4.
[0079] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0080] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0081] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0082] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0083] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0084] Comparative Example 2 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0085] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0086] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0087] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0088] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0089] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0090] Step 2), 36kg of sodium secondary alkyl sulfonate, 75kg of lauramide propyl hydroxysulfobetaine, 61kg of nonanediol monomethyl ether, and 172kg of water are put into a stirring tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, and ultrasonically vibrated for 20min with an ultrasonic power of 1650W.
[0091] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0092] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0093] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0094] Lauramidopropyl hydroxysulfobetaine is commercially available, CAS number: 13197-76-7.
[0095] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0096] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0097] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0098] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0099] Comparative Example 3 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0100] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0101] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0102] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0103] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0104] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0105] Step 2), 36kg of secondary alkyl sodium sulfonate, 75kg of coconut oil diethanolamide, 61kg of dodecyl trimethyl ammonium chloride, and 172kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, and ultrasonically vibrated for 20min with an ultrasonic power of 1650W.
[0106] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0107] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0108] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0109] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0110] Dodecyltrimethylammonium chloride is commercially available, CAS number: 112-00-5.
[0111] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0112] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0113] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0114] Comparative Example 4 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0115] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0116] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0117] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0118] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0119] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0120] Step 2), 36kg of fatty alcohol polyoxyethylene ether sodium sulfate, 75kg of lauramide propyl hydroxysulfobetaine, 61kg of dodecyltrimethylammonium chloride, and 172kg of water are put into a stirring tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, and ultrasonically vibrated for 20min with an ultrasonic power of 1650W.
[0121] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0122] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0123] Sodium fatty alcohol polyoxyethylene ether sulfate is commercially available, CAS number: 9004-82-4.
[0124] Lauramidopropyl hydroxysulfobetaine is commercially available, CAS number: 13197-76-7.
[0125] Dodecyltrimethylammonium chloride is commercially available, CAS number: 112-00-5.
[0126] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0127] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0128] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0129] Comparative Example 5 A lithium slag recycled concrete comprising the following components: Water, cement, modified lithium slag, fine aggregate, recycled coarse aggregate, water reducing agent.
[0130] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0131] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0132] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0133] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0134] The modification method of modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder.
[0135] Step 2), 36kg of sodium secondary alkyl sulfonate, 75kg of coconut oil diethanolamide, 61kg of nonane glycol monomethyl ether, and 172kg of water are put into a stirred tank at a speed of 120r / min and stirred for 5min to form a modified liquid, and then 172kg of lithium slag powder is put into the modified liquid at a speed of 120r / min and stirred for 5min to immerse the lithium slag powder in the modified liquid, heated to 55°C, at a speed of 120r / min, and stirred for 20min.
[0136] Step 3), filtering through 800 mesh filter cloth, taking filter residue, and drying the filter residue in an oven at 110° C. to obtain modified lithium slag.
[0137] The lithium slag was purchased from Guangxi Tianyuan New Energy Materials Co., Ltd. The main chemical components (w / %) of the lithium slag are as follows: Si02: 56.82%, Al203: 23.14%, S03: 9.23%, Ca0: 6.86%, Fe203: 1.22%, K20: 0.39%, MgO: 0.24%, Na20: 0.25%, others: 1.85%.
[0138] Sodium secondary alkyl sulfonate is commercially available, CAS number: 68037-49-0.
[0139] Coconut oil diethanolamide is commercially available, CAS number: 68603-42-9.
[0140] Nonanediol monomethyl ether is commercially available, CAS number: 6048-68-6.
[0141] The preparation method of lithium slag recycled concrete is as follows: Step 01), 142.5kg cement, 142.5kg modified lithium slag, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring tank at a speed of 120r / min and stirred for 15min to obtain a premix.
[0142] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0143] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0144] Comparative Example 6 A recycled concrete comprising the following components: Water, cement, fine aggregate, recycled coarse aggregate, water reducing agent.
[0145] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0146] The fine aggregate was river sand, which was commercially available and had a mesh size of 20-40.
[0147] The recycled coarse aggregate is commercially available and is made from waste concrete with a particle size of 10-15 mm.
[0148] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0149] The preparation method of recycled concrete is as follows: Step 01), 285kg cement, 455kg fine aggregate, 630kg recycled coarse aggregate, and 4.6kg water reducer are put into a stirring kettle at a speed of 120r / min and stirred for 15min to obtain a premix.
[0150] Step 02), add 100kg water to the premix, rotate at 120r / min, stir for 5min, and obtain concrete mixture.
[0151] Step 03), pouring the concrete mixture into a mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing until the 7th day, and standing and curing until the 28th day to obtain lithium slag recycled concrete.
[0152] Experiment 1 According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 7-day compressive strength and 28-day compressive strength of the test samples made of the concrete mixtures prepared in each embodiment and comparative example were tested.
[0153] The specific test data of Experiment 1 are shown in Table 1.
[0154] Table 1 According to the data comparison of each embodiment and the comparative example in Table 1, it can be obtained that the compressive strength of each embodiment is higher than that of comparative example 6. It can be seen that after the lithium slag powder is modified by using a modified liquid prepared by sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water, under the premise of a lithium slag powder dosage of up to 50%, not only can the strength of the concrete not be reduced, but the strength of the concrete can also be increased.
[0155] The strength of comparative examples 1-4 is significantly lower than that of comparative example 6. It can be seen that after the lithium slag powder is modified by other modifying liquids, the strength of the concrete will still be greatly reduced when the lithium slag powder is added in an amount of up to 50%.
[0156] The strength of comparative example 5 is lower than that of comparative example 6. It can be seen that the strength of concrete can be better improved with the cooperation of modifying liquid and ultrasonic vibration. After canceling ultrasonic vibration, the strength of concrete will still decrease to a certain extent if the modifying liquid is used alone.
[0157] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lithium slag recycled concrete, characterized in that: The composition includes the following components in parts by weight: 100 parts water; 140-145 parts of cement; 140-145 parts of modified lithium slag; 450-460 parts of fine aggregate; 625-635 parts of recycled coarse aggregate; Water reducing agent 4.5-4.7 parts; The modification method of the modified lithium slag is as follows: Step 1), grinding the lithium slag to 200-230 mesh to obtain lithium slag powder; Step 2), mixing lithium slag powder and modifying liquid, immersing the lithium slag powder in the modifying liquid, and ultrasonically vibrating for 15-25 minutes; Step 3), filtering and drying to obtain modified lithium slag; In the step 2), the modified liquid is a compound of sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water.
2. The lithium slag recycled concrete according to claim 1, characterized in that: The mass ratio of the sodium secondary alkyl sulfonate, coconut oil diethanolamide, nonanediol monomethyl ether and water is 33-39:72-78:58-64:163-181.
3. The lithium slag recycled concrete according to claim 2, characterized in that: In the step 2), the ultrasonic power is 1500-1800W.
4. The lithium slag recycled concrete according to claim 3, characterized in that: In the step 2), the lithium slag powder and the modified liquid are mixed, heated to 50-60° C., and then subjected to ultrasonic vibration.
5. The lithium slag recycled concrete according to claim 1, characterized in that: The mass ratio of the cement to the modified lithium slag is 1:
1.
6. The lithium slag recycled concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
7. The lithium slag recycled concrete according to claim 1, characterized in that: The fine aggregate is 20-40 mesh.
8. The lithium slag recycled concrete according to claim 7, characterized in that: The particle size of the recycled coarse aggregate is 10-15 mm.
Citation Information
Cited By
High-strength concrete prepared from lithium slag powder and preparation method of high-strength concrete
CN120247493A
Concrete mixing plant
CN120921518A
Modified lithium slag for concrete
CN121850411A
